The impact of immediate adverse donation reactions on the return of volunteers undergoing platelet apheresis. (August 2022) - de Farias, Cássio Lins Gil; Bassolli, Lucas; Mendrone-Junior, Alfredo; de Araújo Arrais, Cyntia; Duran, Amanda; Rocha, Vanderson; de Almeida-Neto, Cesar
Abstract: Introduction: Immediate adverse reactions experienced during donation decrease return rates among whole-blood donors, but little is known about this effect among platelet apheresis donors. We investigated the impact of immediate adverse reactions on the return rates of volunteer apheresis platelet donors. Methods: In a sample of 4108 consecutive platelet apheresis donors seen from August 2016 through June 2019, we evaluated whether immediate adverse reactions were associated with returning for a subsequent platelet apheresis donation within a 12-month period. We used propensity score matching to compare donors with and without adverse reactions. Results: An immediate adverse reaction occurred in 312 (7.6%) donors; 98.5% were mild, and 0.3% were severe. Of the original 4108 platelet apheresis donors, only 3211 (72.3%) returned for a subsequent donation within 12 months. Experiencing an immediate adverse reaction during the donation process significantly decreased the return rate for a subsequent donation [HR= 0.74 (0.63–0.87)], especially among female donors [HR= 0.70 (0.53–0.93)], donors aged < 30 years [HR= 0.71 (0.54–0.94)], with a high school educational level [0.63 (0.49–0.81)], donors donating for the first time [HR= 0.73 (0.59–0.90)], and repeat donors with a previous platelet apheresis donation more than 180 days prior [HR= 0.68 (0.50–0.93)]. Conclusion: Even mild adverse events reduce the return rates for a subsequent donation among platelet apheresis donors. Female donors, younger donors, and first-time donors are at higher risk of not returning after an immediate adverse reaction. Preventing the incidence of immediate adverse reactions during platelet apheresis donation may increase the rate of donor retention.